Changes in Sexual Behavior Related to the COVID-19 Stay-at-Home Orders Among Young Black Men Who Have Sex With Women in New Orleans, LA. Issue 8 (August 2021) - Craig-Kuhn, Megan Clare; Schmidt, Norine; Scott, Glenis; Gomes, Gérard; TatahMentan, Mom; Enaholo, Ososese; Guzman, Stephanie; Tannis, Ayzsa; Hall, Jacob; Triggs, Daniel R.; Kissinger, Patricia J.
Abstract : Background: COVID-19 stay-at-home orders enacted in New Orleans, LA on March 16, 2020, may have caused changes in the way young men interacted with sex partners. Methods: An online substudy was conducted (May 21, 2020 to June 9, 2020) among Black men who have sex with women, 18 years and older, and who had previously enrolled in the parent study Check It (May 17, 2017 to March 6, 2020) to assess changes in sexual behavior during the stay-at-home orders. Results: Among 111 participants, from enrollment in Check It to during stay-at-home orders, recent vaginal sex declined from 96.4% to 47.8% ( P < 0.0001), reports of multiple female sex partners declined from 45.0% to 14.4% ( P < 0.0001), and sexual abstinence increased from 3.6% to 38.7% ( P < 0.0001). Among those who did have vaginal sex, condomless sex rates did not change between enrollment in Check It and the substudy (64.5% vs 67.9%, P = 0.68). During stay-at-home orders oral sex, virtual sex, and pornography viewing were 40.5%, 42.3%, and 76.6%, respectively. Some (17.1%) acquired a new sex partner during stay-at-home orders, and 44.1% left their home to meet a partner for sex. Only 27.9% had seen information about safe sex during the pandemic. Income was diminished for 62.2% and 23.4% moved away from New Orleans when stay-at-home orders were enacted. Conclusions: Although there was an overall reduction in physical sex, half of participants reported physical sex, with many leaving their home to have sex during stay-at-home orders and many not using condoms. Others adopted sexual abstinence, increased virtual sex, and/or pornography viewing, which may have protected them from both sexually transmitted infections and COVID-19. Abstract : Young Black men who have sex with women reported less physical sex and fewer partners during COVID-19 stay-at-home orders, although half were still having sex, and condomless sex was frequent.